Quality assessment on storage of sweetened nata de coco produced by the Salvacion Small Coconut Farmers and Producers Association (SSCFPA) in Buenavista, Guimaras - Inderio, Belen Paderog (1996.)
Sweetened nata de coco produced by the Salvacion Small Coconut Famrers and Producers Association (SSCFPA) in Buenavista, Guimaras was assessed in terms of its quality.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Nata de coco; Salvacion Small Coconut Famrers and Producers Association (SSCFPA) in Buenavista, Guimaras